1996
DOI: 10.1111/1523-1747.ep12345821
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Deletion Mutation in the Gene Encoding the 180-kDa Bullous Pemphigoid Antigen (BPAG2) in a Family with Generalized Atrophic Benign Epidermolysis Bullosa

Abstract: The 180-kDa bullous pemphigoid antigen (BPAG2) is a candidate gene/protein for mutations in some forms of junctional epidermolysis bullosa. In this study, we searched for mutations in BPAG2 in a large Austrian pedigree with generalized atrophic benign epidermolysis bullosa, a distinct nonlethal form of junctional epidermolysis bullosa, using polymerase chain reaction amplification of genomic DNA, heteroduplex analysis of the polymerase chain reaction products, and direct nucleotide sequencing. We identified a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 23 publications
2
38
0
1
Order By: Relevance
“…In vivo subepidermal blistering is observed when expression of BP180 is reduced or absent because of gene knockout in mice or mutation in humans with generalized atrophic benign epidermolysis bullosa (6,49). Van den Bergh and colleagues (50) demonstrated that in cells that lack other hemidesmosomal components, cell matrix attachment is directly related to the amount of BP180 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo subepidermal blistering is observed when expression of BP180 is reduced or absent because of gene knockout in mice or mutation in humans with generalized atrophic benign epidermolysis bullosa (6,49). Van den Bergh and colleagues (50) demonstrated that in cells that lack other hemidesmosomal components, cell matrix attachment is directly related to the amount of BP180 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The proband, a 56-year-old woman, is a member of a large Austrian GABEB kindred that includes 5 affected and 5 unaffected siblings in 1 generation, as well as a pedigree that signifies propagation of the mutant allele through at least 6 generations (18,21). All 4 living affected siblings (1 affected having died in infancy because of complications of this inherited blistering disease) are homozygous for a 2-bp deletion in COL17A1, 4003delTC, and show the same homozygous haplotype for 5 intragenic COL17A1 polymorphisms (17,18,22). The proband's skin shows the same extent and character of blistering as that of her affected siblings; i.e., regions of nonfragile skin are not present.…”
Section: Methodsmentioning
confidence: 99%
“…14). In the largest GABEB kindred identified to date, affected individuals are homozygous for a 2-bp deletion, 4003delTC, which results in a frameshift and a premature termination codon (PTC) 86 bp downstream (17,18). This mutation results in nonsense-mediated mRNA decay that abolishes synthesis of type XVII collagen and accounts for the absence of this adhesion molecule in the epidermal BM of these patients (18).…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4). Most are null mutations resulting in premature termination codons and, subsequently, in nonsense-mediated mRNA decay, whereas some missense mutations and small deletions have been reported (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%